Evaluación genética de búfalos de la raza Murrah para la producción de leche en el día de control y a los 305 días de lactancia - Aspilcueta Borquis, R. [UNESP]; Ramirez-Díaz, J. [UNESP]; Seno de Oliveira, L. [UNESP]; Muñoz Berrocal, M.; Hurtado-Lugo, N. [UNESP]; Galvão de Albuquerque, L. [UNESP]; Tonhati, Humberto [UNESP] (My University, 2009)
There were analyzed 4757 complete lactations of the Murrah breed, daughters of 187 bulls, with the goal of verifying the viability upon employing the test-day (PDLC), on substitution of the milk yield at 305th day of lactation (PL305), in the genetic evaluations. The components of variance for the PDLC1 to PDLC9 and for the PL305 were estimated in uni-traits analysis according to maximum restricted likelihood method. The used model included the genetic direct additive random effects, of residual and permanent environment. There were considered as fixed effects, the contemporary group and the number of milkings and the age of the cow at the moment of parity co-variable (quadratic and linear effect). The contemporary groups were constituted by the herd-year-month of control for the PDLC and by herd-year-epoch of parity for PL305. The estimates of heritability for the PDLC and PL305 were 0.12 to 0.23 and 0.22, respectively. The correlations of order of the predicted genetic values for the 187 bulls, obtained between the PDLC and the PL305, were from moderate to high, varying from 67.74 to 83.12. From the minimum selection of the 10% of the best bulls relating to the predicted genetic value for the PL305, the coincidence among the classification of these animals was over 68%, when evaluated by the PDLC3,PDLC4,PDLC5 and PDLC6. Upon selecting the 5% of the best animals that coincidence presented a lower value.
Genetic evaluation of Murrah buffaloes for lactation yield on the Test-Day and after 305 days of lactation
Keywords: Correlations; Genetic evaluation; Profits; Animalia; Bubalus